A study of the Presbyterian Church mission in the Transvaal from 1903-1960 - Boyd, Barry Graeme (Rhodes University, Faculty of Divinity, Department of Divinity, 1981)
The aim of Â·this study is to present a picture of the circumstances and the manner in which the mission was undertaken. With this in mind reference has been made to individual men and their particular importance and also to the decislons of the Church Assembly as they affected Mission. In part, the thesis is fuller for the earlier years, for the writer holds that these were the most formative as they established the pattern. Furthormore the writer wishes to make clear that the Mission become the work of black men with the white Mission Secretary of the 1950's filling an administrative role. This does not mean he was unimportant but for the nature of this study and its desire to Â·emphasise the role of the black man, the work of these individual administrators has been largely omitted. In the concluding chapters the writer has shown the effects of political changes and African Nationalism on the Mission with a further chapter on the Mission's educational work.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Presbyterian Church -- South Africa -- Transvaal; Missions -- South Africa -- Transvaal